The Magnates of Polish-Lithuanian Commonwealth in 16th-18th century: towards Sejmiks. Ciechanowiec May 24-27, 2022 - GOSZCZYŃSKI, Artur (Historia i Świat, 2022)
Overview and description of the 6th edition of Scientific Conference “The Magnates of Polish-Lithuanian Commonwealth in 16th-18th century” in Ciechanowiec (2022.05.24-27).